On the Origin of the Old Toponyms of the Lviv Region (Materials for the Historical-Etymological Dictionary) 35-41 (Linguostylistic Studies, 2020)
The article is devoted to the linguistic analysis of the settlements’ names of Lviv region: Bibrka, Bitlia, Borynia, Velyke Kholodno, Verkhnia Lukavytsia, Horodysko, and Demnia, which differ from other oikonyms of this region by their chronological and derivational features. The non-slavic proprietary materials were used to explain some names. The article presents brief etymology descriptions of the described in the article Lviv toponyms.Oikonym Bíbrka (fixed at the beginning of the 13th century) is motivated by the corresponding microtoponym, which, in turn, is genetically reduced to the Proto-Slavic *bobrъkъ (beaver).The name of the village of Bítlya (known from the middle of the 16th century), which over time changed from Butlya, we relate to the Ukrainian dialect adjective býtlyavy 'empty', 'rotten inside' ~ verb býtlіti, butliet 'to rot'.Oikonym Borynia (mentioned in the historical sources of the middle 16th century) most likely, originated from the local similar hydronym Borynia (basin of Dniester). But, etymologizing these onyms, the researchers suggest the opposite process, that is, oikonym → hydronym.Oikonym Velyke Kholodno (documented at the end of the 14th century) is motivated by an identical adjective. Compare, for example, Old Russian kholodny, which refers to a deck, and Old Ukrainian kolodnyi in the phrase zєml # kolodnaya (a piece of land in the forest with logs (hemp), set aside for breeding bees).We consider the oikonym Verkhnia Lukavitsa (known since the end of the 18th century) as a derivative, which is motivated by the local (micro) toponym Luka (o) viy (-a, -e) + formant -tsa, and that, in its turn, occured as a result of onimization of the corresponding appellatives, which denoted curvature, bends (of rivers, streams, streams, etc.).Oikonym Horodysko (documented in 1569 as Hrodzysko) we qualify as a derivative of the geographical appellative horodysko/городисько.Oikonym Demnia (recorded in written historical monuments since 1453) researchers etymologize in different ways: a) the settlement used to be constantly in smoke (Ukrainian “zadimlene”); b) the name is motivated by the word domnytsia (furnace for smelting iron from swamp ore); c) most likely came from the appellative demnia (chimney (in the smithy).Thus, both the features of the word-formation models and phonetic modifications of the analyzed onyms in time have been traced on the materials of the documented historical fixations of the oldest oikonyms of the Lviv region.
Keywords: anthroponym; personal name; patronym; appellative; oikonym; onimization